Characteristics of Amino Acid, Fatty Acid and Mineral of Sea Hare - Benny Manulang; Sri Purwaningsih; Azrifitria Azrifitria (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2016)
Dolabella auricularia are found in the waters of Indo - Pacific and has active compound in health,which until now is still limited information about nutritional content from sea hare. The aim of this researchwere to determine morphometric and chemical characteristic D. auricularia which includes the proximate,amino acids, fatty acids and minerals. The composition of fatty acid were measured by gas chromatography(GC), amino acids were measured by high performanced liquid chromatography (HPLC), and mineral wasmeasured by atomic absorption spectrophotometer (AAS). The sea hare contained 9 essential amino acidsand 6 non essential amino acids. The highest essential amino acid was arginine (1.61%) while the highestnon essential amino acids was glycine (3.02%). Sea hare contained 26 fatty acids such as saturated fattyacids 5.33%, monounsaturated fatty acids 2.11% and polyunsaturated fatty acids 4.10%. The high mineralwas calcium 68100 mg/kg.